4102 Assessment of ivermectin-treated backyard chickens as a novel urban West Nile virus prevention strategy - Karen Holcomb; Chilinh Nguyen; Brian D. Foy; Christopher M. Barker (Journal of Clinical and Translational Science, 2020)
OBJECTIVES/GOALS: We conducted a randomized field trail to evaluate the efficacy and safety of a novel vector control strategy that involves treating urban backyard chickens with ivermectin (IVM), a widely used antiparasitic and mosquitocial drug. The goal was to reduce vector mosquito populations and West Nile virus (WNV) transmission. METHODS/STUDY POPULATION: We placed eight flocks—four treated and four untreated control—of six Lohmann brown chickens (16 month-old) each in backyard coops across Davis, CA and administered IVM in feed daily at treated coops (200 mg IVM/kg feed) for eleven weeks. We monitored entomological indices weekly (i.e. mosquito abundance, WNV infection prevalence, and parity rate) in Culex mosquito populations near (10 m) and far (150 m) from each coop location for the peak WNV transmission season (Jul-Sep 2019). We also monitored serum IVM levels in treated chickens and tested for WNV antibodies in all chickens throughout the study. RESULTS/ANTICIPATED RESULTS: Since IVM impacts only mosquitoes that live long enough to take a bloodmeal from a treated chicken, we do not expect to find a marked difference in adult Culex abundance between the two treatment arms, but we expect to find a reduction in WNV infection prevalence and a shift in female mosquito age structure towards younger, uninfected individuals at treated coops. We also anticipate seroconversions in treated chickens to occur at lower rates versus untreated control chickens indicating a reduction in WNV transmission intensity at treated coops. We observed no negative health outcomes from the long-term ingestion of IVM by study chickens. A pathological investigation is underway to compare histological findings between treated and untreated chickens. DISCUSSION/SIGNIFICANCE OF IMPACT: IVM provides the potential for targeted mosquito control. Reduced WNV transmission dynamics here is a stepping stone to a commercial WNV control strategy; IVM-treated feed for wild birds for homeowners’ use to combat WNV transmission in their neighborhoods.